2023
DOI: 10.1002/adhm.202203397
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine‐Based Metabolism Normalization and Oxidative Stress Alleviation by Self‐Assembled Bilirubin/V9302 Nanoparticles for Psoriasis Treatment

Abstract: Psoriasis is an immune-mediated chronic inflammatory skin disorder characterized by epidermal hyperplasia and infiltration of inflammatory cells. Even though the pathogenesis remains unclear, T helper 17 (Th17) cells-mediated inflammation and keratinocyte-involved proliferation are considered to play key roles during the occurrence and the development of psoriasis. Therefore, suppressing the infiltration/function of Th17 and the abnormal hyperplasia of keratinocytes can be a rational strategy for ameliorating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Bilirubin (BR), a yellow bile pigment and the final metabolite of the heme catabolic pathway, was once considered a potentially harmful substance that indicates jaundice. However, it is actually a potent endogenous antioxidant that can scavenge various ROS, protecting cells and the body from oxidative stress‐mediated damage 19,49–54 . BR binds to multiple cellular targets and transduces cellular signalling during metabolic homeostasis, and numerous studies have reported its antioxidant and anti‐inflammatory effects on inflammatory diseases 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Bilirubin (BR), a yellow bile pigment and the final metabolite of the heme catabolic pathway, was once considered a potentially harmful substance that indicates jaundice. However, it is actually a potent endogenous antioxidant that can scavenge various ROS, protecting cells and the body from oxidative stress‐mediated damage 19,49–54 . BR binds to multiple cellular targets and transduces cellular signalling during metabolic homeostasis, and numerous studies have reported its antioxidant and anti‐inflammatory effects on inflammatory diseases 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…BRNP were prepared using a modified nanoprecipitation method. 11 In brief, 2 mg of BR was dissolved in 1 mL of dimethyl sulfoxide (DMSO) to obtain a BR solution of 2 mg/mL. A BR solution was added to 1 mL of double-distilled water in 10 batches (10 μL each) to obtain the preliminary nanoparticles (BRn).…”
Section: Methodsmentioning
confidence: 99%
“…BRNP were prepared using a modified nanoprecipitation method . In brief, 2 mg of BR was dissolved in 1 mL of dimethyl sulfoxide (DMSO) to obtain a BR solution of 2 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoriasis has also been linked to dysregulation of the antioxidant system and increased ROS production. At present, psoriasis may not be completely cured, but the disease process can be alleviated through available treatment methods, including topical therapies, 15,16 phototherapy, 17 systemic medications, and biologics, which can help alleviate symptoms and improve the quality of life for individuals with the condition. 18 For example, several traditional immunosuppressive drugs, such as TNF-α, IL-17, and IL-23 inhibitors, have demonstrated high efficacy in treating psoriasis vulgaris.…”
Section: Introductionmentioning
confidence: 99%